Membandingkan Hermeneutika dengan Ilmu Tafsir - Achmad Khudori Soleh (TSAQAFAH, 2011)
Hermeneutic as interpretation knowledge can be classified into three categories: objective, subjective, and liberation. 1). Objective hermeneutic means an effort to interpret and to understand the meaning of text as the author means. 2). Subjective hermeneutic means an effort to interpret and to understand the meaning of text based on the social context at this time without any consideration to the author thought. 3). Liberation hermeneutic means an effort to interpret and to understand the meaning of text based on the spirit of circumstance and try to make the result of interpretation as the spirit to change the life and the circumstance of the interpreter and the reader. In Islamic perspective, objective hermeneutic can be compared with tafsir bi al-ma’tsur, and subjective hermeneutic can be compared with tafsir bi al-ra’y. However, hermeneutical discourse has been giving much contribution for the development of interpretation knowledge, so it can appear hermeneutic of liberation. It is a new penetration. If it is applied in Islam, interpretation does not only understand the meaning of al-Qur’an text as God means or based on the context, but also an effort how to make the result of interpretation as the spirit for Muslim society to change their society become better and the best.